2023
DOI: 10.1097/sle.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Common bile duct (CBD) Diameter After Laparoscopic Cholecystectomy (LC) and Laparoscopic Common Bile Duct Exploration (LCBDE)

Abstract: Background: Common Bile duct (CBD) measurement is a crucial aspect in the evaluation of the biliary tree. Whether the CBD undergoes any compensatory change in diameter after laparoscopic cholecystectomy or laparoscopic common bile duct exploration is still up for discussion. The aim of this study was to investigate CBD diameter changes after laparoscopic cholecystectomy (LC) and laparoscopic common bile duct exploration (LCBDE) on magnetic resonance cholangiopancreatography (MRCP).Materials and Methods: Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…This coped with what was mentioned by Park et al, (10) that a CBD dilatation within 10 mm in gallbladder resected patients can be regarded as normal physiological change. The results also kept up with what was stated by Pallaneeandee et al, (11) that this post-cholecystectomy dilatation can be attributed to compensatory adaptation of the CBD in the absence of the gallbladder. In our study, biliary stones weren't only detected in GB but also in CBD and hepatic ducts (group III patients).…”
Section: Introductionsupporting
confidence: 88%
“…This coped with what was mentioned by Park et al, (10) that a CBD dilatation within 10 mm in gallbladder resected patients can be regarded as normal physiological change. The results also kept up with what was stated by Pallaneeandee et al, (11) that this post-cholecystectomy dilatation can be attributed to compensatory adaptation of the CBD in the absence of the gallbladder. In our study, biliary stones weren't only detected in GB but also in CBD and hepatic ducts (group III patients).…”
Section: Introductionsupporting
confidence: 88%
“…Studies have shown that a high stone removal rate can be attributed to the use of choledochoscopy, electrohydraulic lithotripsy (EHL), and a balloon dilation system [ 15 ]. Although intraoperative ultrasound and cholangiography are helpful in the detection of common bile duct stones [ 18 , 19 ], EHL and laser lithotripsy can significantly improve the stone removal rate. However, residual stones inevitably present in a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high risk of postoperative complications related to ERCP + LC may be due to the sphincter of Oddi incision during the surgical procedure, which may cause changes in the biliary tract structure that negatively affect the natural defense mechanism of the bile duct, leading to adverse events, such as pancreatitis, hyperamylasemia, BTI, and bile leakage[ 22 , 23 ]. The LC + LCBDE approach, as a one-time operation, circumvents the high surgical risk of two procedures in the ERCP + LC approach and preserves duodenal papilla function, thus avoiding the structural changes to the bile duct related to the papillotomy and infections caused by retrograde flow of intestinal juice[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%